Efficiency Performance of GCC Insurance Sector - Rossazana, Ab-Rahim; Asif, Ahmed; Nur Nadhira, Baharuddin (Human Resource Management Academic Research Society, 2021)
The objective of this study is to analyse the efficiency performance of Takaful and conventional in GCC insurance sector for the period 2015 to 2019. Data Envelopment Analysis (DEA) were used to estimate the efficiency level. Premium and investment income are taken as common output variable while labour, total fixed assets, business services, and equity capital as major input. The results show that the Takaful firms are equally efficient compared to the conventional firms. The Takaful when compared to conventional insurance is highly technical and pure technical efficient however it is moderately cost efficient and there is a large opportunity for improvement.